2012
DOI: 10.1088/1674-1056/21/1/010303
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic iteration approach to supersymmetric bistable potentials

Abstract: We examine quasi exactly solvable bistable potentials and their supersymmetric partners within the framework of the asymptotic iteration method (AIM). It is shown that the AIM produces excellent approximate spectra and that sometimes it is found to be more useful to use the partner potential for computation. We also discuss the direct application of the AIM to the Fokker—Planck equation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Unfortunately, it could only be possible for a very limited number of potentials such as harmonic oscillators, Coulomb, Kratzer potentials and so on [16] with a centrifugal term for l = 0. In this way, there are several established analytical methods, including Polynomial solution [16,18,19], Nikiforov-Uvarov method (NU) [20], Supersymmetric quantum mechanics method (SUSY QM) [21,22], and Asymptotic iteration method (AIM) [23][24][25][26][27][28][29], in order to solve analytically the radial Schrödinger equation for l = 0 within various potentials. G.Levai et al suggested a simple method for the proposed potentials for which the Schrödinger equation can be solved exactly with special functions [30] and presented relationship between the introduced formalism and supersymmetric quantum mechanics [21].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, it could only be possible for a very limited number of potentials such as harmonic oscillators, Coulomb, Kratzer potentials and so on [16] with a centrifugal term for l = 0. In this way, there are several established analytical methods, including Polynomial solution [16,18,19], Nikiforov-Uvarov method (NU) [20], Supersymmetric quantum mechanics method (SUSY QM) [21,22], and Asymptotic iteration method (AIM) [23][24][25][26][27][28][29], in order to solve analytically the radial Schrödinger equation for l = 0 within various potentials. G.Levai et al suggested a simple method for the proposed potentials for which the Schrödinger equation can be solved exactly with special functions [30] and presented relationship between the introduced formalism and supersymmetric quantum mechanics [21].…”
Section: Introductionmentioning
confidence: 99%
“…Along the years, there was a huge amount of research effort to solve exactly the radial Schrödinger equation for all values of n r and l quantum numbers, but it could only be possible for a few specific potentials. In this way, there are several established analytical methods, including Polynomial solution [1][2][3], Nikiforov -Uvarov method (NU) [4], Supersymmetric quantum mechanics method (SUSYQM) [5,6], and Asymptotic iteration method (AIM) [7][8][9][10][11][12][13], to solve the radial Schrödinger equation exactly or quasi-exactly for l = 0 within these potentials. G.Levai et al suggested a simple method for the proposed potentials for which the Schrödinger equation can be solved exactly with special functions [14] and presented relationship between the introduced formalism and SUSYQM [5].…”
Section: Introductionmentioning
confidence: 99%
“…In this study we will apply a new formalism based on the Taylor series expansion method, namely, asymptotic Taylor expansion method (ATEM) [22], to bistable potentials. These type of potentials have been used in the quantum theory of molecules as a crude model to describe the motion of a particle in the presence of two centers of force [23][24][25][26][27][28][29]. It is mentioned in [22] that the taylor series Method [30,31] is an old one but it has not been fully exploited in the analysis of both physical and mathematical problems in solution.…”
Section: Introductionmentioning
confidence: 99%